Bringing Porous Framework Materials toward Photocatalytic H2O2 Production - Bao, Chen-Hao; Li, Lan; Wang, Xiao-Fei; Xia, Sa-Sa; Wang, Xusheng; Jin, Cheng-Chao; Chen, Zhi (Nano letters, 2025)
Photocatalytic H2O2 production driven by renewable solar energy is a promising and sustainable approach, with porous framework materials such as metal–organic frameworks (MOFs), covalent organic frameworks (COFs), and hydrogen-bonded organic frameworks (HOFs) emerging as highly efficient catalysts. This Review first presents the current research state of porous framework materials in H2O2 photosynthesis, focusing on the progress in H2O2 production across different porous frameworks and mechanism insights gained through advanced techniques. Furthermore, a systematic categorization of material modifications aimed at enhancing the photocatalytic efficiency is provided, linking structural modifications to improved H2O2 production performance. Key factors such as charge carrier separation and transfer, reaction pathways, and material stability are comprehensively analyzed. Finally, the challenges related to stability, scalability, and cost-effectiveness, are discussed alongside opportunities for future advancements. This Review aims to provide insights into understanding and optimizing porous framework materials for efficient and scalable H2O2 photosynthesis.